THE IMPACT OF SHEEP MANURE UTILIZING AS AN INNOVATIVE PRODUCT “BIOSLURRY PLUS TRICHODERMA (BIOS +)” ON BINA MANDIRI FARMER GROUP IN PULOSARI VILLAGE, SUKABUMI DISTRICT - Emmia Tambarta Kembaren; Mawardati; Yusra; Romano; Ramayana (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2023)
Fertilizer scarcity is still a major problem in agriculture in Indonesia. Furthermore, to overcome the scarcity of fertilizers, the use of chemical fertilizers is expected to be replaced by using organic fertilizers such as Bio Slurry. This innovative product could solve the problem of fertilizer scarcity that occurs among farmers in Indonesia. The utilization of sheep manure to produce innovation product “Bioslurry Plus Trichoderma (BIOS +)” is a program of CSR from PT PLN Indonesia Power PLTP Gunung Salak Kamojang POMU in the form of community development activities. The location of community service was taken at the Bina Mandiri group in Pulosari Village, Kalapanunggal District, Sukabumi Regency. The implementation methodology is designed for mentoring with a participatory approach which consists of: (1) Providing information related to the benefits of innovative products BIOS +, (2) Providing information how to make and apply BIOS +, (3) Practice of applying BIOS + on their cultivated land, and (4) Observation the impact of using BIOS + on soil conditions, cost efficiency, changes in knowledge and changes in behavior of Bina Mandiri group. According to the BIOS+Innovation production implemented by CSR PT PLN Indonesia Power PLTP Gunung Salak Kamojang POMU, the following conclusions are: 1) Bina Mandiri has been successfully maximized their asset in this program, 2) the BIOS + empowerment program resulted in a reduction of chemical fertilizer use on their cultivated land by 185 kg, 3) The improvement of soil and environmental conditions after using BIOS+ from the total land owned by 15 members is 4.14 hectares of horticultural crops, 4) the efficiency of reducing the cost of chemical fertilizers per 3 months is IDR 3,700,000, 5) the Increase in of Bina Mandiri Group's technical knowledge in producing BIOS+ after program implementation is 100%. This exceeded the program's target, and 6) the increase in behavior to apply the innovation product BIOS+ in Bina Mandiri Group is 60%. This exceeded the program's target.